Kiss-induced severe anaphylactic reactions - Atanasković-Marković Marina; Živanović Mirjana; Gavrović-Jankulović Marija; Ćirković-Veličković Tanja; Đurić Vojislav; Sanković-Babić Snežana; Nestorović Branimir (Srpski Arhiv za Celokupno Lekarstvo, 2010)
Introduction. Ingestion is the principal route for food allergens to trigger allergic reaction in atopic persons. However, in some highly sensitive patients severe symptoms may develop upon skin contact and by inhalation. The clinical spectrum ranges from mild facial urticaria and angioedema to life-threatening anaphylactic reactions. Outline of Cases. We describe cases of severe anaphylactic reactions by skin contact, induced by kissing in five children with prior history of severe anaphylaxis caused by food ingestion. These cases were found to have the medical history of IgE mediated food allergy, a very high total and specific serum IgE level and very strong family history of allergy. Conclusion. The presence of tiny particles of food on the kisser's lips was sufficient to trigger an anaphylactic reaction in sensitized children with prior history of severe allergic reaction caused by ingestion of food. Allergic reaction provoked with food allergens by skin contact can be a risk factor for generalized reactions. Therefore, extreme care has to be taken in avoiding kissing allergic children after eating foods to which they are highly allergic. Considering that kissing can be a cause of severe danger for the food allergic patient, such persons should inform their partners about the risk factor for causing their food hypersensitivity.